2020
DOI: 10.1016/j.molcel.2020.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Inhibited State of the Sec Translocon

Abstract: Summary Protein secretion in eukaryotes and prokaryotes involves a universally conserved protein translocation channel formed by the Sec61 complex. Unrelated small-molecule natural products and synthetic compounds inhibit Sec61 with differential effects for different substrates or for Sec61 from different organisms, making this a promising target for therapeutic intervention. To understand the mode of inhibition and provide insight into the molecular mechanism of this dynamic translocon, we determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
120
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(135 citation statements)
references
References 76 publications
(118 reference statements)
12
120
3
Order By: Relevance
“…Consistent with this unusual membrane topology, we found no indication that the membrane insertion of any of our OPG2-tagged ORF6 variants was reduced by Ipom-F, strongly suggesting that its association with the inner leaflet of the ER membrane does not require protein translocation via the central channel of the Sec61 translocon ( Gérard et al, 2020 ). We noted a subset of OPG2–ORF6–OPG2 species bearing only a single N-glycan was also clearly present in the membrane-associated fraction with or without Ipom-F treatment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this unusual membrane topology, we found no indication that the membrane insertion of any of our OPG2-tagged ORF6 variants was reduced by Ipom-F, strongly suggesting that its association with the inner leaflet of the ER membrane does not require protein translocation via the central channel of the Sec61 translocon ( Gérard et al, 2020 ). We noted a subset of OPG2–ORF6–OPG2 species bearing only a single N-glycan was also clearly present in the membrane-associated fraction with or without Ipom-F treatment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It seems likely that viral type II TMPs will also be inhibited by Ipom-F (cf. Morel et al, 2018; Zong et al, 2019; Gérard et al, 2020) but, since SARS-CoV-2 has no such proteins, we have not addressed this issue.…”
Section: Resultsmentioning
confidence: 99%
“…94 Interestingly, the mutations conferring resistance to mycolactone clustered in the same region, 73 suggesting that structurally different Sec61α inhibitors share a common binding site and mode of action. Gérard et al 95 recently reported an electron cryo-microscopy structure of mycolactone bound Sec61α. Surprisingly, the mycolactone-binding pocket did not overlap with the region identified by resistance mutations, suggesting that such mutations may induce conformational changes indirectly preventing mycolactone binding.…”
Section: F I G U R Ementioning
confidence: 99%